Metabolic characteristics of non-obese and obese metabolic dysfunction-associated fatty liver disease in type 2 diabetes mellitus and its association with diabetic peripheral neuropathy and diabetic retinopathy - Dang, Si-Wen; Gao, Lei; Li, Yu-Jun; Zhang, Ruo; Xu, Jing (Frontiers in Medicine, 2023)
Aim To assess the metabolic characteristics of non-obese metabolic dysfunction-associated fatty liver disease (MAFLD) compared with obese MAFLD and the relationship of MAFLD with diabetic peripheral neuropathy and diabetic retinopathy in patients with Type 2 diabetes mellitus (T2DM). Methods Data were obtained from 536 T2DM patients (355 women, 181 men; age 58.2 ± 12.0 years). We explored the difference in clinical characteristics between obese MAFLD (body mass index ≥25 kg/m2) and non-obese MAFLD (body mass index <25 kg/m2) in T2DM patients. One-way analysis of variance (ANOVA) was used to compare the means of continuous variables, and the Chi-squared test was used to compare the differences in frequencies of categorical variables. Logistic regression models were adopted to calculate odds ratios. Results The prevalence of MAFLD in hospitalized Chinese T2DM patients was calculated to be 42.7%. Both obese and non-obese MAFLD patients had higher levels of body mass index (BMI), waist circumfere nce, triglyceride, alanine aminotransferase, aspar tate aminotransferase, γ-glutamyltransferase, you nger age, higher prevalence of hyperlipidemia and shorter duration of T2DM and lower incidence of diabetic retinopathy, compared with participants with out MAFLD in the same weight group. Uric acid levels were positively correlated with the risk of MAFLD only in non-obese subjects but not in obese subjects. In non-obese patients with T2DM, a negative correlation was found between the prevalence of MAFLD and diabetic retinopathy. Conclusion Even in non-obese patients with T2DM, BMI was found to be an independent risk factor for MAFLD. These findings support a more structured, risk-factor-based approach to MAFLD management, particularly in patients with T2DM. Non-obese MAFLD has unique results in metabolic characteristics and the correlation with diabetic retinopathy and diabetic peripheral neuropathy, which should be further explored.